Delay Optimization for PBFT Based on Alternative Voting Mechanism - WU Xiaotong, LIU Pingzeng (Ji suan ji gong cheng, 2021)
The Practical Byzantine Fault-Tolerance(PBFT) algorithm is limited by the high latency of consensus, inefficient view switching and lack of dynamicity.To address the problems,an improved algorithm called IPBFT with lower delay based on alternative voting mechanism is proposed.By adding an alternate set,the algorithm enables the number of consensus nodes in the system to be dynamically adjusted.At the same time,the view switching protocol is improved to allow the algorithm to complete the consensus process in only two phases,reducing the communication overhead of the system.On this basis,the way of selecting the primary node is changed to a voting election mechanism, which realizes primary node election in the process of node consensus to reduce the number of communication times and latency required for view switching.The experimental results show that the IPBFT algorithm has lower consensus delay and higher throughput than the original PBET algorithm.Meanwhile,it can support the nodes to dynamically join or exit.